The Concept of Medieval Stasis: From Medieval Studies to Medievalism, from Medievalism to Political Culture - Maksym W. Kyrchanoff (Журнал Фронтирных Исследований)
The purpose of the article is to analyze the principles of intellectual history of medieval stasis, borrowed from academic medieval studies and brought into modern mass cultural medievalism. The article analyzes, on the one hand, the problems of gradual revision of the theory of medieval stasis in academic historiography, and on the other hand, the features of its positive idealization in medievalism. It is shown that modern medievalism could not fully assimilate the concept of medieval stasis, integrating into intellectual discourse only those of its aspects that allow constructing the image of the Middle Ages as an exceptionally stable period, when social and political changes were not only impossible, but also were unnecessary. It is shown that 1) the concept of medieval stasis in modern historiography is gradually perceived as part of the intellectual history of the medieval studies, 2) medievalism perceives the stability of feudal structures as its positive characteristic, 3) the use of the concept of medieval stasis in modern medievalism allows to construct the preservation of chronologically prolonged images of Middle Ages, 4) within the framework of the idealization of the Middle Ages, modern medievalist discourse synthesizes the “real” and the “magical”, which excludes the development of narrative structure and the transformation of social, economic and political relations and institutions, 5) the archaic vision of the Middle Ages through the prism of stasis confirms the limitations of the cognitive capabilities of medievalism.